Patterns of Fine Ash Dispersal Related to Volcanic Activity at West Mata Volcano, NE Lau Basin - Walker, Sharon L.; Baker, Edward T.; Lupton, John E.; Resing, Joseph A. (Frontiers in Marine Science, 2019)
Extensive deep (>1500 m) non-hydrothermal ash-rich plumes were present in the water column surrounding West Mata submarine volcano (NE Lau basin) during eruptive phases, but were absent when West Mata was quiescent. Deep ash plumes were chemically distinct from hydrothermal plumes originating at West Mata and other hydrothermal sources in the region, and were dominated by very fine shards compositionally similar to the lava erupting at the ∼1200 m summit with morphologies indicative of magma degassing and shattering. Deep ash plume layers occurred at variable water depths (and distances above the seafloor) and were transported by local currents to 10s of km from West Mata. We interpret these deep ash plumes to be syn-eruptively generated ash transported downslope via sediment gravity flows of varying magnitudes, runout distances, and liftoff densities. Final deposition of individual particles will be by settling from suspension (i.e., fallout deposits). The mechanism for initiating gravity flows is uncertain, but their spatial and temporal distribution suggests that eruption column collapse and/or mobilization of unstable volcaniclasts accumulating on steep slopes during the eruption are likely sources. Turbidity within the deep ash plumes decreased by 80% over a 3 week period in 2017, suggesting the eruption that created a new deposit, constrained between March 2016 and November 2017, was likely active as recently as a few weeks to months prior to the FK171110 expedition. Similar deep ash plumes have been observed surrounding other erupting submarine volcanoes. This pattern of syn-eruptive dispersal suggests that fine ash does not have to be lofted high into the water column in event plumes, or enter the ocean from subaerial sources, to be dispersed by local currents and contribute to fallout deposits in regional and distal sediments, which may appear as cryptotephra or thin ash layers if the ash supply exceeds pelagic sedimentation rates; deposits that are often attributed to subaerial eruptions alone. These results also suggest that the presence of deep ash plumes surrounding a submarine volcanic edifice, along with a magmatic-hydrothermal plume above the summit, may be a valuable diagnostic exploration tool for identifying active, or very recently active, submarine eruptions.